2013
DOI: 10.3357/asem.3728.2013
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue Assessment: Subjective Peer-to-Peer Fatigue Scoring

Abstract: The research basis for scientific validity and reliability regarding current peer fatigue scoring systems is exiguous. This novel approach may be of merit, particularly among military aircrew in a deployed-type setting with sustained high workload, operational stress, and limited time for supernumerary tasks. An anonymous subjective peer-to-peer fatigue scoring system is worthy of further scientific investigation, particularly warranting studies of reliability and validity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…Objective assessments of performance decline due to fatigue hold significant scientific merit in terms of reliability and validity. However, translating various laboratory-based psychomotor or neurocognitive tests into practical tools for quantifying risk assessment presents challenges, particularly when it comes to the diverse skill sets required for ensuring flight safety (Gaydos et al, 2013). Subjective rating scales also hold scientific value, as there are numerous self-reported fatigue assessment instruments with different levels of complexity and accuracy.…”
Section: Subjective Measures Of Fatiguementioning
confidence: 99%
See 1 more Smart Citation
“…Objective assessments of performance decline due to fatigue hold significant scientific merit in terms of reliability and validity. However, translating various laboratory-based psychomotor or neurocognitive tests into practical tools for quantifying risk assessment presents challenges, particularly when it comes to the diverse skill sets required for ensuring flight safety (Gaydos et al, 2013). Subjective rating scales also hold scientific value, as there are numerous self-reported fatigue assessment instruments with different levels of complexity and accuracy.…”
Section: Subjective Measures Of Fatiguementioning
confidence: 99%
“…Another approach involves using peer-rating scales. (Gaydos et al, 2013) initiated a new peer-to-peer system for rating fatigue subjectively, where pilots anonymously provide a weekly (or other appropriate time interval) score to rate the fatigue of all other pilots in the unit. The scoring system uses a simple 1-10 Likert-type scale with specific instructions for each rank to ensure consistent subjective assessment.…”
Section: Two Well-known and Validated Subjective Scales For Measuring...mentioning
confidence: 99%
“…Fatigue can also negatively affect the pilot's performance, decreasing attention capacity and flexibility (Caldwell, 1997;Farrell et al, 2016). Landing is usually the final task for the pilot coming back from a mission, and it requires an increased cognitive effort after a less demanding cruising period (Gaydos et al, 2013;Hartzler, 2014).…”
Section: Pilot Factorsmentioning
confidence: 99%
“…Courtney et al conducted sleep restriction and deprivation experiments and concluded that all scales are effective for fatigue detection [2]. Gaydos et al [3] proposed an approach not only based on pilots themselves but also their peers' perspectives. Useche et al [4] studied the relationships among fatigue, work-related and stress-related conditions, and dangerous driving behaviors.…”
Section: Introductionmentioning
confidence: 99%